Assessing Postural Risks in the Building Construction Sector: A Case Study in Bangladesh - Md. Sumon Rahman; Md. Kutub Uddin; Mohammad Iqbal (International Journal of Occupational Safety and Health)
Introduction: Among the different parts of the construction sectors, the building sector needs more workers for materials handling because of the absence of proper infrastructural facilities. Work-related musculoskeletal disorders (WRMSDs) can occur due to awkward body postures and repetitive and long-term contact of body parts with this activity. The main aim of this study was to evaluate the body posture risk levels among building construction workers in Bangladesh.